Awareness about antibiotic resistance in a self-medication user group from Eastern Romania: a pilot study - Topor,Gabi; Grosu,Ionela-Alina; Ghiciuc,Cristina Mihaela; Strat,Aurel Lulu; Lupuşoru,Cătălina Elena (PeerJ, 2017)
Background Awareness about antibiotic resistance depends on the attitudes and information about antibiotic resistance of both patients and physicians. Persons who practice self-medication are at high risk of also self-medicating with antibiotics. The purpose of the present study was to evaluate the awareness about antibiotic resistance by investigating the practice in a group of self-medication users in a sample of adults in Romania and the variables associated with such practice. Material and Methods A cross-sectional self-filled questionnaire based study was conducted from December 2016 through January 2017 amongst 218 self-medication users (SMUG). The attitudes, the level of knowledge, the perceptions, about antibiotic use (ABU) and about antibiotic resistance (ABR) were compared to a reference group represented by medical residents group in their specialty training (MRG) considered to have a higher level of knowledge and awareness about ABU and ABR. Results The response rate was 87.2% in the SMUG group and 100% in the MRG group. The SMUG group reported self-medication practices for antibiotics with a high frequency at any time in life (72%), but with a very low frequency from the month previous to the date of the study (12%), comparative with the MRG group (75% and 7%, respectively). The multivariate logistic regression analysis showed that self-medication with antibiotics at any time in life in the SMUG group could be predicted by the answers to two questions regarding the practices and knowledge about ABU (Q13 and Q20). On the other hand, in the MRG group, a question about ABR perception (Q23), could be predictor for self-medication with antibiotics. Self-medication with antibiotics in the month previous to the date of the study in the SMUG group could be predicted with three questions: one about ABU practice (Q14), one about ABR perception (Q26) and one referring to ABR knowledge (Q28). On the other hand, in the MRG group, a question about ABR knowledge (Q32) could be predictor for self-medication with antibiotics. The reduced awareness about ABR in the SMUG group, is revealed by the reduced number of subjects (38%), who did not know that missing an antibiotic dose during a medical treatment contributes to ABR, comparative with the MRG group (84%). Indirectly, low ABR awareness in the SMUG group is revealed by the confusion about the appropriate use of antibiotics in bacterial or viral infections (that antibiotics are not used against viruses). Conclusions The findings from our study on the awareness about antibiotic resistance in the SMUG group might help the policy makers and regulatory authorities to develop educational programs directed to change the perceptions and attitudes about the appropriate use of antibiotics in order to diminish self-medication practices with antibiotics.
Keywords: Antibiotic bacterial resistance; Self medication users; Practices; Awareness; Attitudes; Health knowledge; General population; Medical residents